Periprocedural Management of Patients Undergoing Liver Resection or Embolotherapy for Neuroendocrine Tumor Metastases. Issue 4 (April 2019) - Kwon, Daniel H.; Paciorek, Alan; Mulvey, Claire K.; Chan, Hilary; Fidelman, Nicholas; Meng, Lingzhong; Nakakura, Eric K.; Zhang, Li; Bergsland, Emily K.; Van Loon, Katherine
Abstract : Objectives: The objective of this study was to describe the periprocedural management of patients with well-differentiated neuroendocrine tumors with hepatic metastases who underwent liver-directed procedures. Methods: We performed a retrospective review of patients with metastatic neuroendocrine tumors who underwent liver resection, ablation, or embolotherapy at a single center from 2012 to 2016. The primary outcome was occurrence of documented carcinoid crisis (CC) or hemodynamic instability (HDI), defined as 10 minutes or more of systolic blood pressure less than 80 or greater than 180 mm Hg, or pulse greater than 120 beats per minute. Results: We identified 75 patients who underwent liver resection/ablation (n = 38) or embolotherapy (n = 37). Twenty-four patients (32%) experienced CC or HDI (CC/HDI); CC occurred in 3 patients. No clinicopathologic or procedural factors, including procedure type, octreotide or long-acting somatostatin analog use, and history of carcinoid syndrome, were associated with CC/HDI. Grades 2 to 4 complications were reported in 42% of patients who experienced CC/HDI versus in 16% of patients who did not experience CC/HDI ( P < 0.05). Conclusions: A significant portion of patients developed CC/HDI, and these patients were more likely to develop severe postprocedural complications. Periprocedural octreotide use was not associated with lower CC/HDI occurrence, but continued use is advised given its safety profile until additional studies definitively demonstrate lack of benefit.